2020
DOI: 10.1021/acssuschemeng.0c07699
|View full text |Cite
|
Sign up to set email alerts
|

Workability and Rheological Property Evolution of Active Rejuvenated Styrene–Butadiene–Styrene-Modified Bitumen in the Early Stage

Abstract: To improve the performance of rejuvenated styrene− butadiene−styrene (SBS)-modified bitumen mixture and realize its highvalue recycling, active rejuvenators and biorejuvenators were combined to regenerate the aged SBS-modified bitumen. The effect of active rejuvenators on the workability of active rejuvenated SBS-modified bitumen (ARSMB) was studied; meanwhile, the evolution of rheological properties and chemical structure of ARSMB in the early stage was also investigated comprehensively. The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Due to the long-term exposure to high temperature, light, and oxygen, the SBS molecular structure in SBSMA is susceptible to a CC bond breakage, resulting in the formation of polar carboxyl and carbonyl functional groups and polymer radicals . Binary reactive chemical reagents (HMDI and HDE) will be utilized in this study to effectively link the polymer radicals and thus reorganize the SBS molecular structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the long-term exposure to high temperature, light, and oxygen, the SBS molecular structure in SBSMA is susceptible to a CC bond breakage, resulting in the formation of polar carboxyl and carbonyl functional groups and polymer radicals . Binary reactive chemical reagents (HMDI and HDE) will be utilized in this study to effectively link the polymer radicals and thus reorganize the SBS molecular structure.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the long-term exposure to high temperature, light, and oxygen, the SBS molecular structure in SBSMA is susceptible to a C�C bond breakage, resulting in the formation of polar carboxyl and carbonyl functional groups and polymer radicals. 23 Binary reactive chemical reagents (HMDI and HDE) will be utilized in this study to effectively link the polymer radicals and thus reorganize the SBS molecular structure. Figure 2 shows the chemical reactions of HMDI and HDE with the fragmented SBS molecular structure, where (1)−(4) represent the chemical reactions of HMDI with broken chains of SBS, (1) and ( 2) are the hydroxyl and carboxyl group linkage reactions with isocyanate, respectively, (4) represents the reaction of isocyanate with the small amount of water present in aged asphalt, and ( 5) and ( 6) are reactions between the hydroxyl and carboxyl groups attached to epoxy functional groups.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Relatively, the benzene ring structures in HMDI adversely affected the low-temperature performance. Besides, Cao et al found that the isocyanate reaction was affected by curing time and temperature. Specifically, higher curing temperature and longer curing time could significantly build up the performance of aged SBS modified bitumen.…”
Section: Rejuvenation Of Aged Sbs Modified Bitumen By Repairing Degra...mentioning
confidence: 99%
“…Given that different reactive chemicals had different reaction mechanisms and rejuvenation effectiveness, some scholars attempted to add different reactive chemicals to restore the performance of aged SBS modified bitumen. , Due to the findings that MDI and HDI were beneficial to enhance the high-temperature and low-temperature performance respectively, Cao et al applied HDI, MDI, and cashew shell oil to rejuvenate aged SBS modified bitumen. Apart from the addition of similar chemicals, Xu et al applied the compound reactive rejuvenators containing BUDGE and MDI in the rejuvenation of aged SBS modified bitumen because BUDGE and MDI can improve low-temperature cracking resistance and high-temperature rutting resistance, respectively.…”
Section: Rejuvenation Of Aged Sbs Modified Bitumen By Repairing Degra...mentioning
confidence: 99%
See 1 more Smart Citation